Analysis of Escherichia coli Extended-Spectrum Beta-Lactamase ESBL Bacteria in Chicken Farm Waste in Cipondoh, Tangerang City - Wartiani, Wartiani; Maulida, Aulia; Puspitasari, Riris Lindiawati; Jumianto, Syafitri (RSF Conference Series: Business, Management and Social Sciences, 2023)
Antibiotics are a class of drugs that stop biochemical processes in an organism, stop the growth of bacteria, and naturally create an immune system for the body. The result of using the wrong antibiotics is the occurrence of antibiotic resistance, which means that microorganisms can survive against antibiotics given later. The problem of antibiotic resistance can be spread through livestock, one of which is chicken, one of the most important benefits of chicken farming. In this regard, research was conducted on analysing the number of E. coli bacteria in chicken farms in the Cipondoh area, Tangerang City. E. coli from livestock waste is one of the microorganisms that can combine with ESBL causing antibiotic resistance. Antibiotic resistance is dangerous if it occurs in humans who consume livestock products and spreads to the environment through the waste discharged into the environment. Antibiotic resistance will cause antibiotics to be unable to prevent disease anymore so that diseases are immune and already resistant to antibiotics. Research on the presence of ESBL bacteria in E. coli present in livestock waste needs to be studied further so that the incidence of antibiotic resistance can be prevented and can be followed up as early as possible so that antibiotic resistance or immunity to antibiotics can be prevented as soon as possible and does not become a threat and new epidemics for humankind in the future and humans do not abuse the use of antibiotics against livestock.